Application of near infrared spectroscopy to exercise sports science - Neary, J. P. (Canadian Journal of Applied Physiology, 2004)
Over the past 15 years the use of near infrared spectroscopy in exercise and sports science has increased exponentially. The majority of these studies have used this noninvasive technique to provide information related to tissue metabolism during acute exercise. This has been undertaken to determine its utility as a suitable tool to provide new insights into the heterogeneity and regulation of local tissue metabolism, both in cerebral and skeletal muscle tissue. In the accompanying articles in this symposium, issues related to the principles, techniques, limitations (Ferrari et al., 2004), and reliability and validity of NIRS in both cerebral and skeletal muscle tissue (Bhaambhani, 2004), mostly during acute exercise, have been addressed and will not be discussed here. Instead, the present paper will focus specifically on the application of NIRS to exercise sports science, with an emphasis on how this technology has been applied to exercise training and sport, and how it can be used to design training programs for athletes.